Insights into antiradical mechanism and pro-oxidant enzyme inhibitor activity of walterolactone A/B 6-O-gallate-β-d-pyranoglucoside originating from Euonymus laxiflorus Champ. using in silico study. Issue 46 (19th October 2022) - Quy, Phan Tu; Dzung, Nguyen Anh; Van Bay, Mai; Van Bon, Nguyen; Dung, Doan Manh; Nam, Pham Cam; Thong, Nguyen Minh
Abstract : In silico evaluation of a novel compound isolated from Euonymus laxiflorus Champ. for its ability as a hydroperoxyl radical scavenger and pro-oxidant enzyme inhibitor. Abstract : The ability of a new compound, Wal, (walterolactone A/B 6- O -gallate-β-d -pyranoglucoside) originating from Euonymus laxiflorus Champ. as a hydroperoxyl radical scavenger and pro-oxidant enzyme inhibitor was studied in silico . Different mechanisms, reaction locations, and chemical species of Wal in aqueous solution were taken into consideration. Formal hydrogen transfer from the OH group has been discovered as the chemical process that contributes most to the antioxidant properties of Wal in nonpolar and aqueous solutions. The overall rate coefficients for polar and non-polar environments are expected to have values of 7.85 × 10 6 M −1 s −1 and 4.84 × 10 5 M −1 s −1, respectively. According to the results of the investigation, Wal has greater scavenging activity against the HOO˙ radical than the reference antioxidant Trolox at physiological pH (7.4). In addition, docking results indicate that Wal 's antioxidant properties involve the inhibition of the activity of enzyme families (CP450, MP, NO, and XO) that are responsible for ROS production.